Quality Difference Study of Six Varieties of Ganoderma lucidum with Different Origins - Lu, Juan; Qin, Jia-zhang; Chen, Ping; Zhao, Si-jia (Frontiers in Pharmacology, 2012)
The quality difference of 6 varieties Ganoderma Lucidum with different origins was investigated in this study by comparing the contents of ganoderic acid A and B, polysaccharide and triterpenoids .The contents of ganoderic acid A and B in G.lucidum were analysed by ultra performance liquid chromatography (UPLC). There was higher content of ganoderic acid A in G.lucidum of Dabie Mountain and Longquan. The G.lucidum from Longquan has the highest content of ganoderic acid B. The content of polysaccharide was determined by Anthrone-sulfuric acid method. The highest of polysaccharide content is G.lucidum from Liaochen. The content of triterpenoid in G. lucidum was quantified by ultraviolet spectrophotometer at 548.1 nm using Ursolic acid as standard. The G.lucidum from Dabie Moutain has the highest content of triterpenoids. In summary, the content of ganoderic acid A and B, polysaccharide and triterpenoids in G.lucidum with different origins are remarkably different, which may be caused by the conditions of cultivation and geographic environment.